Ebola virus dynamics in mice treated with favipiravir - Madelain, Vincent; Oestereich, Lisa; Graw, Frederik; Nguyen, Thi Huyen Tram; de Lamballerie, Xavier; Mentré, France; Günther, Stephan; Guedj, Jeremie (Antiviral research, 2015)
The polymerase inhibitor favipiravir is a candidate for the treatment of Ebola virus disease. Here, we designed a mathematical model to characterize the viral dynamics in 20 mice experimentally infected with Ebola virus, which were either left untreated or treated with favipiravir at 6 or 8days post infection. This approach provided estimates of kinetic parameters of Ebola virus reproduction, such as the half-life of productively infected cells, of about 6h, and the basic reproductive number which indicates that virus produced by a single infected cell productively infects about 9 new cells. Furthermore, the model predicted that favipiravir efficiently blocks viral production, reaching an antiviral effectiveness of 95% and 99.6% at 2 and 6days after initiation of treatment, respectively. The model could be particularly helpful to guide future studies evaluating favipiravir in larger animals.
Gesehen am 04.06.2020